Key Indicators Affecting Hospital Efficiency: A Systematic Review - Imani, Ali; Alibabayee, Roghayeh; Golestani, Mina; Dalal, Koustuv (Frontiers in Public Health, 2022)
Background: Measuring hospital efficiency is a systematic process to optimizing performance and resource allocation. The current review study has investigated the key input, process and output indicators which are commonly used in measuring the hospital’s technical efficiency to promote the accuracy of the results. Methods: To conduct this systematic review, the electronic resources and databases MEDLINE (via PubMed), Scopus, Ovid, Proquest, Google Scholar and reference lists of the selected articles were used for searching articles between 2010 to 2019. After in-depth reviews based on the inclusion and exclusion criteria, among 1537 studies, 137 articles were selected for the final assessment. CASP tool was used for evaluating the quality of the articles. The main findings of studies have been extracted using content analysis. Results: After final analysis, the Context/Input indicators that were commonly considered by studies in analyzing hospital technical efficiency include different variables related to Hospital Capacity, Structure, Characteristics, Market concentration and Costs. The Process/Throughput indicators include different variables related to Hospital Activity/services-oriented process Indicators, Hospital Quality-oriented process indicators and Hospital Educational Process. And finally, the Output/Outcome indicators include different variables related to Hospital Activity- related output variables and Quality- related output/outcomes variables. Conclusion: This study has identified that it is necessary to mix and assess a set of input, process, and output indicators of the hospital with both quantitative and qualitative indicators for measuring hospitals’ technical efficiency comprehensively.